The high rate of long-term recurrences and sequelae after epistaxis treatment - Kindler, Rahel M.; Ditzen, Beate (Auris, nasus, larynx, 2016)
Objective Epistaxis is the most frequent rhinologic emergency with a high treatment morbidity. This study assessed the long-term outcome after epistaxis treatment with regard to patient comfort during the treatment, long-term complications and rate of recurrences. Methods A questionnaire cohort study was performed at the ENT department of the University Hospital Zurich. In April 2014, 363 patients were contacted, who were treated between March 2007 and April 2008 for the reason of epistaxis using a written questionnaire to elucidate the patients’ condition after the treatment. The type of treatment, subjective discomfort as well as degree of pain, complications, permanent sequelae and recurrences were assessed. Results 109 questionnaires were analyzed (response rate of 36%). The overall same-sided recurrence rate after successful treatment during the 6.4-year follow-up was 22%. Discomfort was reported in 48% after cautery, 86% after packing and in 11% after surgery. Strong or very strong pain was perceived in 8% after cautery, 26% after packing and in 0% after surgery alone. Complications consisted of nasal crusting in 15% after cautery and nasal breathing impairment in 24% after packing. Permanent harm was reported in 4% after cautery versus 20% after packing plus surgery. Conclusions The data confirm the high rate of recurrences despite adequate treatment in the long-term analysis. The rate of post-treatment complications is considerably high with nasal crusting being the main inconvenience. It further shows that patients keep a vivid memory of the treatment even many years later and that packing is extremely uncomfortable to patients.